The millipede type specimens in the Collections of the Field Museum of Natural History (Arthropoda: Diplopoda) - Sierwald, Petra; Bond, Jason E.; Gurda, Grzegorz T. (Zootaxa, 2005)
Field Museum’s Millipede Collection currently comprises 376 type lots for 208 species. Types of the millipede orders Glomeridesmida (4 species), Sphaerotheriida (2 species), Polyzoniida (1 species), Platydesmida (7 species), Siphonophorida (8 species), Stemmiulida (10 species), Chordeumatida (17 species), Polydesmida (103 species), Spirobolida (33 species), Spirostreptida (19 species), and Julida (4 species) are represented. The collection contains type specimens of species described by the authors Bond & Sierwald (3 species), Chamberlin (95 species), Golovatch (1 species), Golovatch, Vohland & Hoffman (4 species), Hoffmann (8 species), Keeton (1 species), Loomis (85 species), Mauriès (2 species), Shear (4 species), Shear & Leonard (1 species), Shelley (1 species), Vohland (1 species), and Wesener & Sierwald (2 species). Amplinus fortinus Chamberlin, 1952 (Polydesmida: Aphelidesmidae) is identified as a nomen nudum. The millipede type material is separated from the main collection and vials are organized by order in jars. All lots are indentified with a unique collection number. Specimen data are cataloged and maintained in a Microsoft Excel spreadsheet. The collection catalog is slated to be moved to a relational database (KE-EMU) within the next few years.